INVESTIGATION OF THE INFLUENCE OF VIBRATION DURING THE MACHINING PROCESS (Conference Zone, 2022)
In this article, the formulation of the concept of vibration is studied and outlined its impact on humans and equipment in production. Methods of dealing with vibration have been studied and analyzed.